Setting time evaluation of injectable carbonate apatite cement using various sodium carboxymethylcellulose (Na CMC) concentration - Cahyanto, Arief; Permatasari, Indah; Febrida, Renny (Padjadjaran Journal of Dentistry, 2018)
Introduction: The injectable calcium phosphate cement has the advantage to be used in the bone defect with the limited access which supports a minimally invasive surgical technique. These Injectability properties of calcium phosphate cement can be modified by adding a sodium carboxymethylcellulose (Na CMC). The aim of this present study is to investigate the setting time of injectable bone cement based on CO3Ap using various Na CMC concentration. Methods: Vaterite (a polymorph of CaCO3) and Dicalcium Phosphate Anhydrous (DCPA) as powder phase mixed with 0.2 mol/L Na2HPO4 solution containing 1% polyethylene glycol (PEG) and various concentration of Na CMC as followed 0.5%, 1%, 1.5%, and 2%, respectively. Each concentration groups was consisting of 5 samples from total 20 samples. Powder and liquid phase was mixed with a spatula at a liquid to powder (L/P) ratio of 0.4. The setting time of CO3Ap cement was evaluated according to the modification method standardized by ISO 1566 for dental zinc phosphate cement using a custom fabricated Vicat needle apparatus. The cement was maintained at 37ÂºC and 100% relative humidity as a standard requirement. Results: The mean value of setting time cement was as followed 0.5% Na CMC 35:06 minutes, 1% Na CMC 38:48 minutes, 1.5% Na CMC 40:06 minutes, and 2% Na CMC 41:30 minutes. The result is statistically significant (p<0.05) with the group of 0.5% Na CMC compared to others group. Conclusion: Increasing the concentration of Na CMC could prolong the setting time of CO3Ap cement.